Characteristics of nursing homes associated with COVID‐19 outbreaks and mortality among residents in Victoria, Australia. (19th July 2021) - Ibrahim, Joseph E.; Li, Yingtong; McKee, Grace; Eren, Hagar; Brown, Charlotte; Aitken, Georgia; Pham, Tony
Abstract: Objective: To determine nursing home characteristics associated with COVID‐19 outbreak, outbreak size and mortality, during the second wave in Victoria, Australia. Method: Population‐based cross‐sectional study of all nursing homes in Victoria between 7 July and 13 November 2020. Results: There were one or more resident cases of COVID‐19 in 9.7% of nursing homes (74/766). COVID‐19 intrusion was more likely in larger metropolitan facilities, privately owned by large chains, with a past history of regulatory non‐compliance, located close to high‐risk industry. Larger outbreaks were associated with homes in metropolitan areas, accommodating 91 or more residents, with shared rooms, owned by private providers operating many (11 or more) facilities. The highest case‐fatality rates were observed in homes owned by not‐for‐profit providers operating many facilities, located close to high‐risk industry. Conclusion: Stratifying nursing homes according to characteristics associated with morbidity and mortality can inform risk management, prioritising emergency responses and optimising future nursing home operations.